Apparent Digestibility and Utilization of Protein and Phosphorus in diets of incorporated with Sprouted Sorghum, Phytase and Protease Enzymes for African Catfi sh (Clarias gariepinus) - Kemigabo C; Kang'ombe J; Jere LW; Sikawa D; Masembe C (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2017)
Apparent digestibility, deposition and retention of crude protein and phosphorus were determined for 30%, 35%, 50% and 55% CP diets incorporated with sprouted sorghum, 750, 1000 and 1250 unitskg-1 phytase and protease enzymes ,fed to African catfish fingerlings. All digestibility coefficients significantly differed (p<0.05) among diets with the (92.66%) observed for phosphorus in 30% and 35%CP diets with 1250 units of phytase, while that of protein (81.49%) was in 50%CP and 55% CP diets with 1250 units of protease. Crude protein deposition and retention significantly differed (p<0.05) with the highest (705.10 and 10.03 respectively) recorded in diets with 1250 protease while that of phosphorus did not in both cases (p>0.05). This demonstrated that protease was more useful in starter (high protein) diets and phytase enzyme in grower (low protein) diets and forms a basis for efficient use of phytase and protease enzymes in catfish diet formulations for different growth stages.